219k views
3 votes
Rewrite the rational expression as an equivalent rational expression with the given denominator

Rewrite the rational expression as an equivalent rational expression with the given-example-1

1 Answer

2 votes

Let z be the required expression.

The given is


(3)/(14x+98)=(z)/(14y(x+7))

Using the cross product method, we get


3*14y(x+7)=z(14x+98)


42y(x+7)=z(14x+98)

Dividing both sides by 14x+98, we get


(42y\mleft(x+7\mright))/(14x+98)=(z\mleft(14x+98\mright))/(14x+98)


(42y\mleft(x+7\mright))/(14(x+7))=z


(42y)/(14)=z


3y=z

Hence the answer is


(3)/(14x+98)=(3y)/(14y(x+7))

User YoniLavi
by
5.2k points